Distribution of 10-formyltetrahydrofolate synthetase in eubacteria. - Whitehead, T R (1988)
The distribution of 10-formyltetrahydrofolate synthetase, which activates formate for use as a one-carbon donor in a variety of biosynthetic reactions, was determined for a variety of eubacteria. Organisms from several genera were found to lack detectable synthetase activity; however, all organisms tested were found to contain 5,10-methylenetetrahydrofolate dehydrogenase activity.